Determinant People Development and Employee Performance: Analysis Training, Certification, and Competence - Andi Muhammad Sabilillah Tahir (International Journal of Business and Applied Economics, 2023)
The purpose of this study was to determine the direct relationship of training, certification and competency variables to employee performance mediated by employee development, while the results of this study concluded that there was a direct relationship and used literature studies without research respondents and did not use statistical data processing, in this study there are many findings that can be developed again in further research by other researcher.